Providing Knowledge About the Prevention of Violence among High School Students as an Urgent Problem of Psychology - Abdullaevna, Bakhramova Abira (European Journal of Life Safety and Stability (2660-9630), 2023)
This article explores the problem of violence in the educational environment - violence, which is seen as a phenomenon that in the future leads to serious psychological problems. This problem attracts the attention of not only society, but also science. According to research data, it can be summarized that at the moment the problem of interpersonal relations with elements of violence is becoming a social norm.